The optimal threonine:lysine ratio to maximize growth performance of nursery pigs - James, B.W.; Woodworth, J.C.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 210 pigs (initially 18.2 lb and 25 d of age) were used in a 21-d growth assay. The seven treatments consisted of a basal diet (14.1% CP) with increasing levels of threonine (45, 50, 55, 60, 65, and 70% of 1.07% apparent digestible lysine) and a negative control containing 0.97% lysine. Increasing dietary threonine improved feed efficiency; however, there was no improvement in growth performance between pigs fed 0.97 and 1.07% apparent digestible lysine. Therefore, these results suggest the requirement for apparent digestible threonine is approximately 60% of lysine for 18- to 40-lb pigs.
Keywords: Swine; Threonine; Lysine; Nursery pigs